1986
DOI: 10.1021/jm00159a015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thyrotropin-releasing hormone analogs. 2. Tripeptides structurally greatly different from TRH with high central nervous system activity

Abstract: A new series of thyrotropin-releasing hormone (TRH) analogues, obtained by further modifications of our most potent central nervous system (CNS) stimulating neutral tripeptides at both termini, were synthesized by the pentafluorophenyl ester method and tested for CNS and thyrotropin (TSH) releasing activity. Replacement of pyroglutamic acid by pyro-2-aminoadipic acid, 2-oxoimidazolidine-4-carboxylic acid or gamma-butyrolactone-gamma-carboxylic acid and that of proline by pipecolic acid, thiazolidine-4-carboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…[28][29][30] l-pAad-OPfp (15) was synthesized from commercially available l-Lys(Z)-OH in four steps as described earlier. [31] Boc-1-alkyl-l-His-OH compounds 17 a-e were synthesized from Boc-l-His-OH in one step as reported. [32] (1R)-3-Ocp-OH (20) was synthesized from 4-vinylcyclohexene in four steps and chemically resolved using a well-established procedure.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] l-pAad-OPfp (15) was synthesized from commercially available l-Lys(Z)-OH in four steps as described earlier. [31] Boc-1-alkyl-l-His-OH compounds 17 a-e were synthesized from Boc-l-His-OH in one step as reported. [32] (1R)-3-Ocp-OH (20) was synthesized from 4-vinylcyclohexene in four steps and chemically resolved using a well-established procedure.…”
Section: Resultsmentioning
confidence: 99%
“…This result demonstrated that the presence of histidine is not essential for the CNS activity while, as mentioned above, the steric properties of the amino acid at position 2 are critical in the ligand's hormonal activity. Subsequently, it was shown [49] that further replacement of pyroglutamic acid by pyro-2-aminoadipic acid in addition to replacement of His by Leu or Nval resulted in analogs with prominent CNS activity with little or no hormonal potency.…”
Section: Histidinementioning
confidence: 99%
“…1G) is created by substituting both the pGlu and His residues. Posatirelin is approximately 5 times more potent in regard to its CNS effects than TRH, however its effects on TSH release are diminished 30-fold compared to native TRH (Szirtes et al, 1986; Oka et al, 1989; Culum and Forbes, 2008). Posatirelin has been shown to enhance norepinephrine and dopamine turnover in the cerebral cortex, nucleus accumbens, and striatum, and increase cyclic GMP levels in the cerebellum of rats (Oka et al, 1989).…”
Section: Trh Analogs As Potential Treatments For Neurodegenerativementioning
confidence: 99%